Keanekaragaman Jenis Serangga di Berbagai Lahan Pertanian Kelurahan Maubeli Kabupaten Timor Tengah Utara - Maria Marmi Aveludoni (Wahana-Bio: Jurnal Biologi dan Pembelajarannya, 2021)
The presence of insects in an ecosystem varies widely, the diversity of insects in various agricultural lands can act as polydonature insects, pests, parasites, and predators for other insects. Referring to the role of insects, this study aims to determine what insects are present in various agricultural lands, to analyze insect diversity and to analyze environmental factors that influence the presence of insects. This research was conducted in Maubeli Village, North Central Timor Regency in July-August 2020. The sampling technique was carried out with pitfall traps, light traps and sweep nets, the data obtained were analyzed using the Shannon-Wiener diversity index. The research that has been carried out has found insects at the research location consisting of the families of Acrididae, Coccinelidae, Libellulidae, Mantidae, Nymphalidae, Papiolinidae, Pieridae, and Tettigonidae. The highest diversity of 11 families was found with the highest value H` = 1.34 and the lowest H` = 0.26. The results of measurement of environmental parameters at the research location show that morning, evening and night air temperatures range from 260C-280C, 270C-310C, 250C-360C, and humidity ranges from 60% -70%, soil pH ranges from 6 and soil moisture ranges from 2%.